Increase in antibiotic resistance in diabetic foot infections among peruvian patients: a single-center cross-sectional study - Moya-Salazar, Jeel; Chamana, Jackelina M.; Porras-Rivera, Daniela; Goicochea-Palomino, Eliane A.; Salazar, Carmen R.; Contreras-Pulache, Hans (Frontiers in Endocrinology, 2023)
Background Diabetic foot is one of the most significant complications in individuals with diabetes and is closely associated with lower limb amputation. The antibiotic susceptibility patterns of these bacterial isolates play a critical role in guiding effective treatment strategies We aimed to determine the most common bacterial agents causing diabetic foot infections in a tertiary-care hospital in Peru. Methods Clinical and microbiological data were collected from 181 patients diagnosed with diabetic foot infections and positive microbiological culture results. All the samples were analyzed with the Vitek 2 compact system and the cut-off points were defined with the CLSI M100 guide. The data were segregated based on mono-microbial or poly-microbial cultures, bacterial types, and antibiotic susceptibility profiles. Results A total of 32 bacterial species were identified, predominantly Gram-negative (63%). The most frequent bacterial agents isolated were Staphylococcus aureus (19.9%), Escherichia coli (12.2%), Pseudomonas aeruginosa (8.3%), and Proteus vulgaris (6.6%). These bacteria commonly exhibited resistance to Ampicillin, Ciprofloxacin, Levofloxacin, Trimethoprim-sulfamethoxazole, and Cefuroxime. E. coli showed the highest antibiotic resistance (19 antibiotics), while Gentamicin, Tobramycin, and Levofloxacin demonstrated the highest sensitivity against the most prevalent bacteria. Gram-negative bacteria also exhibited notable antibiotic-susceptibility to Meropenem, Piperacillin/tazobactam, and Amikacin. Regarding the presence of Extended-Spectrum Beta-Lactamase, 54 isolates tested positive, with 35 (64.8%) and 14 (42.4%) of these being S. aureus and E. coli. Conclusions Bacterial agents causing diabetic foot infections pose a constant concern, particularly due to the increasing antibiotic resistance observed. This difficulty in treating the condition contributes to a higher risk of amputation and mortality. Further research on bacterial susceptibility is necessary to determine appropriate dosages for pharmacological treatment and to prevent the overuse of antibiotics.